WOMAN'S STRENGTH AND PATIENCE IN "JANE EYRE", A NOVEL BY CHARLOTTE BRONTE - Fattiyeva Habibaxon Zaynidinovna; Tohirova Umida Akramovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Charlotte Brontë's novel "Jane Eyre" is a literary masterpiece that explores the resilience, strength, and patience of women in the face of adversity. The novel's protagonist, Jane Eyre, serves as a powerful representation of a woman who overcomes challenges, societal constraints, and personal obstacles through her unwavering determination and indomitable spirit. In this article, we will delve into the themes of strength and patience as exhibited by women in "Jane Eyre."This research paper aims to explore the life and literary works of Charlotte Bronte, a prominent 19th-century English novelist. The paper will provide a comprehensive analysis of Bronte's background, influences, and contributions to the literary canon, with a focus on her most famous novel, "Jane Eyre." Additionally, the paper will examine the themes, characters, and narrative techniques in Bronte's works, as well as their impact on the Victorian era and subsequent literary movements. Through a critical exploration of Bronte's literary legacy, this research paper seeks to shed light on her enduring significance in the world of literature.